Fostering Character Development in Elementary School Students: Implementing the Independent Curriculum Through the Pancasila Student Profile Program - Suwarni Suwarni (AL-ISHLAH: Jurnal Pendidikan, 2024)
The implementation of new curricula often encounters challenges, particularly in aligning the understanding of curriculum developers and users. This study addresses the issue of moral degradation among students in Indonesia and the role of the Merdeka Curriculum in fostering the Pancasila Student Profile to mitigate these concerns. This qualitative research utilized observations, interviews, and documentation to explore the application of the Merdeka Curriculum in sekolah penggeraks. Data were analyzed to examine its stages and effectiveness in developing the Pancasila Student Profile. The findings reveal that the six dimensions of the Pancasila Student Profile align with the five principles of Pancasila. The implementation in sekolah penggeraks follows four key stages: preparation, planning, implementation, and evaluation. Habituation practices are integral, divided into routine and spontaneous habituation. These approaches effectively nurture religious character and moral values among students. The Merdeka Curriculum offers opportunities for independent thinking, creativity, and innovation while addressing moral deficiencies. Sekolah penggeraks serve as a critical platform for embedding these values, ensuring the development of well-rounded, character-driven students. The Merdeka Curriculum, when systematically implemented, promotes the formation of the Pancasila Student Profile, which is essential for addressing student moral degradation. This curriculum can be a strategic tool in achieving educational and societal objectives.